Business as usual determining the effects of campaign contributions during the 2016 Philippine National Elections on the stock returns of politically connected firms - Santos, Patrick G. (School of Economics, University of the Philippines Diliman, 2019)
Utang na loob or debt of gratitude is seen as the primary reason that drives crony capitalism in the Philippines. Studies in different countries have shown that there are strong links between politically connected firms and its performance, buying them future firm specific political favors. Our study sought to test the effects of campaign contributions made by publicly listed firms in the stock market to political candidates during the 2016 Philippine national elections. We estimate OLS regressions by using an event study approach, suggesting that firms who contributed to winning candidates, especially to the winning president, experienced significant positive cumulative abnormal stock returns around the election period. Firms are willing to invest in political influence as they expect political favors in return, whether in good or bad times. As such, we implore the government to review its campaign finance laws for transparency and accountability to the Filipino people.